2019
DOI: 10.1037/cap0000080
|View full text |Cite
|
Sign up to set email alerts
|

Examining the high-risk accused designation for individuals found not criminally responsible on account of mental disorder.

Abstract: In 2014, the Canadian government amended the Criminal Code, allowing courts to designate some individuals found not criminally responsible on account of mental disorder (NCRMD) as high-risk accused (HRA). As a result, individuals found HRA face significant new restrictions for transitioning through the forensic system. This study examined the relevance of the HRA designation by simulating the retrospective application of the legislative criteria to the National Trajectory Project (NTP) sample of 1,800 persons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 34 publications
(72 reference statements)
4
11
0
2
Order By: Relevance
“…Moreover, there was no statistically significant difference between the HRA and non-HRA group for violent offenses against the person (hazard ratio [HR] = .95, 95% confidence interval [CI] .69, 1.31, p = .757). Despite the HRA group having slightly higher recidivism rates than the non-HRA group, Goossens et al, (2019) reported that the HRA group spent considerably more time under the supervision of the Review Board than the non-HRA group. Indeed, individuals in the HRA group were nearly two times less likely to receive an absolute discharge (HR = .51, 95% CI .44, .58, p < .001).…”
Section: Not Criminally Responsible Reform Act (Ncrra)mentioning
confidence: 95%
See 2 more Smart Citations
“…Moreover, there was no statistically significant difference between the HRA and non-HRA group for violent offenses against the person (hazard ratio [HR] = .95, 95% confidence interval [CI] .69, 1.31, p = .757). Despite the HRA group having slightly higher recidivism rates than the non-HRA group, Goossens et al, (2019) reported that the HRA group spent considerably more time under the supervision of the Review Board than the non-HRA group. Indeed, individuals in the HRA group were nearly two times less likely to receive an absolute discharge (HR = .51, 95% CI .44, .58, p < .001).…”
Section: Not Criminally Responsible Reform Act (Ncrra)mentioning
confidence: 95%
“…There is a need for a large-scale longitudinal study in Alberta comparing general and violent recidivism rates between persons found NCRMD who committed particularly brutal index offenses with NCRMD persons who did not commit "brutal index offenses." This study, like Goossens et al (2019), could help provide practitioners, researchers, and policy makers the data to help determine institutional best practices for the forensic mental health system. This research could help inform Review Boards across Canada.…”
Section: Limitations and Future Researchmentioning
confidence: 98%
See 1 more Smart Citation
“…Entre las variables clínicas del estudio realizado se destacó la predominancia de los trastornos del espectro de la esquizofrenia (67,0%), aunque los trastornos mentales orgánicos, el retraso mental y las patologías asociadas al consumo de drogas ilegales también resultaron de importancia. Así, la prevalencia de la esquizofrenia en la muestra estudiada (57,5%) fue similar a lo reportado en el estudio colombiano con el 63,0% 6 , pero significativamente superior a los hallazgos de la investigación sueca (33,6%) 30 e inferior a los del estudio canadiense (77,9%) 32 . El estudio llevado a cabo en Turquía mostró la prevalencia de esquizofrenia de 42,5%, siendo esta por debajo del presente estudio, pero la prevalencia de trastornos afectivos (19,5%) fue significativamente superior 33 .…”
Section: Discussionunclassified
“…El único establecimiento penitenciario que cuenta con el servicio de hospitalización psiquiátrica en el Perú es el EP Lurigancho, sin embargo, sus condiciones de atención psiquiátrica no cumplen con las normas técnicas para la atención de salud, según el reporte del Ministerio de Salud 39 . Es importante precisar que, en el Perú, no se cuenta con un adecuado sistema psiquiátrico forense en comparación con otros países [26][27][29][30][31][32]40 .…”
Section: Discussionunclassified